Human blues : a novel - Albert, Elisa, 1978- (Avid Reader Press, an imprint of Simon & Schuster, Inc, 2022)
Aviva Rosner is at a crossroads. Her fourth album is about to be released--and her manager says it's going to be big. But Aviva is focused on getting pregnant, which she can't seem to do. How far will she go to have a child? Is that what she really wants? And what about her music, and her growing obsession with Amy Winehouse?